If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -3) = 8x + 15 Reorder the terms: 5(-3 + x) = 8x + 15 (-3 * 5 + x * 5) = 8x + 15 (-15 + 5x) = 8x + 15 Reorder the terms: -15 + 5x = 15 + 8x Solving -15 + 5x = 15 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -15 + 5x + -8x = 15 + 8x + -8x Combine like terms: 5x + -8x = -3x -15 + -3x = 15 + 8x + -8x Combine like terms: 8x + -8x = 0 -15 + -3x = 15 + 0 -15 + -3x = 15 Add '15' to each side of the equation. -15 + 15 + -3x = 15 + 15 Combine like terms: -15 + 15 = 0 0 + -3x = 15 + 15 -3x = 15 + 15 Combine like terms: 15 + 15 = 30 -3x = 30 Divide each side by '-3'. x = -10 Simplifying x = -10
| 5xn=600 | | 9m-28=2n | | 5a+8-4a=8 | | .1z+.3z=-8 | | (52-9)+n=62 | | 6.48=ln(x) | | 5(3b-3)= | | -7k-16-7k=124 | | -13.1y+4.38=-18.7y+9.9y-2.93 | | w+5+8w+6=29 | | 4n-7+4n=8+8n-5 | | 5x-7y+x+2x-y=0 | | =5(3b-3) | | 5(a+36)=59+156 | | 6(a+4)=6(4-2) | | 139-u=217 | | -19+17u=18u+1 | | 3-x+4x+6-2x+1= | | -2(3x+1)=10 | | -14+18g=16g+14 | | -x+2(-2x+16)=-8 | | x=10.5y | | -x-4x+16=-8 | | x+y+2y+-2x+z+5x-y= | | 6y-3=2y+15 | | 2(x-2)-16=8-2x | | 13q+8=9q | | -x^5+2x^4-4x^3= | | 9x-63=4x+22 | | s+6=8(9) | | 6m+2(m+7)=m | | x-6=66-15(x+8) |